The solace of stones : finding a way through wilderness - Riddle, Julie (American lives., 2016)
"The memoir of a contemporary pioneer family who takes up homesteading in the wilderness of Montana, The Solace of Stones uncovers the complexities of memory, silence, and identity of a young woman who comes to terms with repressed childhood sexual abuse amid the cultural and gender mores enforced by enduring myths of the West"--Provided by publisher.